2024
DOI: 10.1002/cpp.2952
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between treatment integrity and outcome in group psychotherapy: A systematic review

Giovanna Esposito,
Angela Di Maro,
Raffaella Passeggia

Abstract: Treatment integrity is defined as the extent to which the treatment has been implemented according to a specific theoretical model. It consists of two components: adherence, that is, the degree to which the therapist implements the techniques prescribed by the theoretical model, and competence, that is, the degree to which the therapist skilfully and appropriately implements the techniques prescribed by the model. Recently, the issue of integrity is gaining increasing importance in psychotherapy research, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Firstly, it leads therapists to implement different treatments despite guidelines provided by theoretical manuals, characterizing itself as opposed to one of the dimensions of treatment integrity, namely adherence (Stiles, 2021). However, several researchers have shown that therapists can adhere to a treatment protocol and at the same time adapt their interventions to patients' needs (Kendall & Frank, 2018;Marques et al, 2019) with a positive impact on the therapeutic outcome (Esposito et al, 2024;Esposito et al, 2020), supporting the idea that manualized treatments may incorporate methods and techniques of other models (McAleavey & Castonguay, 2014). In this regard, Hatcher (2021) underlines the importance of integrating these two factors in order to tailor the treatment to patients' necessities while remaining within a clear theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it leads therapists to implement different treatments despite guidelines provided by theoretical manuals, characterizing itself as opposed to one of the dimensions of treatment integrity, namely adherence (Stiles, 2021). However, several researchers have shown that therapists can adhere to a treatment protocol and at the same time adapt their interventions to patients' needs (Kendall & Frank, 2018;Marques et al, 2019) with a positive impact on the therapeutic outcome (Esposito et al, 2024;Esposito et al, 2020), supporting the idea that manualized treatments may incorporate methods and techniques of other models (McAleavey & Castonguay, 2014). In this regard, Hatcher (2021) underlines the importance of integrating these two factors in order to tailor the treatment to patients' necessities while remaining within a clear theoretical framework.…”
Section: Introductionmentioning
confidence: 99%